2012
DOI: 10.1007/s11010-012-1476-7
|View full text |Cite
|
Sign up to set email alerts
|

Crocin, a dietary additive protects platelets from oxidative stress-induced apoptosis and inhibits platelet aggregation

Abstract: Platelets are the key players in the development of cardiovascular diseases as the microparticles generated by apoptotic platelets and platelet aggregation contribute actively towards the disease propagation. Thus, the aim of this study was to demonstrate the effect of a phytochemical which can prevent these two processes and thereby project it as a cardio-protective compound. Crocin, a natural carotenoid exhibits a wide spectrum of therapeutic potentials through its antioxidant property. The study demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 33 publications
2
41
0
Order By: Relevance
“…36 Thus, hara et al (2013) suggested that crocin protects platelets from oxidative stressinduced apoptosis through reducing H2O2-evoked activation of caspase-3 (pro-apoptotic protein). 37 Therefore we suggest that the anti-apoptotic effect of crocin may due to antioxidant effects, lowering blood glucose and reduction of p53 protein in pancreas tissue. Finally, in the present study, we found that crocin combination with voluntary exercise have an additive effects on blood glucose, HbA1c and p53 expression levels in pancreas tissue of type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 88%
“…36 Thus, hara et al (2013) suggested that crocin protects platelets from oxidative stressinduced apoptosis through reducing H2O2-evoked activation of caspase-3 (pro-apoptotic protein). 37 Therefore we suggest that the anti-apoptotic effect of crocin may due to antioxidant effects, lowering blood glucose and reduction of p53 protein in pancreas tissue. Finally, in the present study, we found that crocin combination with voluntary exercise have an additive effects on blood glucose, HbA1c and p53 expression levels in pancreas tissue of type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 88%
“…Hence, there is a need for potent molecules that can protect platelets from the premature death. Till date there are only two reports describing the inhibition of platelet apoptosis by phytochemicals namely, cinnamtannin-B1 and crocin [17], [18]. Both the molecules ameliorate the oxidative stress-induced platelet apoptosis by modulating ROS mediated mitochondrial damage.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress occurs where excess ROS overwhelm endogenous antioxidant systems, resulting in damage to many cellular components, including proteins, lipids and nucleic acids, and subsequent apoptosis [21,22]. Hydrogen peroxide is capable of causing oxidative damage to platelet proteins [41], and a recent study demonstrates that riboflavin/UV treatment of platelets induces oxidative modification of selected peptides, such as fibronectin [42], and Mirasol treatment of plasma increases protein carbonylation [15].…”
Section: Discussionmentioning
confidence: 99%
“…As platelets generate ROS during activation [16,17] and ROS are capable of selectively modulating platelet activation [18,19], it is imperative to understand the role of Mirasol treatment in this context to ensure a complete understanding of the toxicological profile of this component [20]. Persistent high levels of ROS may overwhelm endogenous antioxidant systems, resulting in damage to proteins, lipids, and nucleic acids leading to apoptosis [21,22]. …”
Section: Introductionmentioning
confidence: 99%